Crop Yield and Yield Stability as Affected by Long-Term Tillage and Nitrogen Fertilizer Rates in Dryland Wheat and Sorghum Production Systems - M. Majrashi; A. K. Obour; C. J. Moorberg (Kansas Agricultural Experiment Station Research Reports, 2019)
A major challenge for agronomists is developing cropping systems that exhibit superior performance across variable environmental conditions, especially precipitation. Long-term field research trials provide a direct measure of the effect of environmental conditions within the context of treatment effects. Here we investigated the impact of tillage practices and nitrogen (N) rates on yields for dryland wheat and sorghum as influenced by weather and precipitation. The study focused on a long-term (40 years) tillage and N fertilizer experiment established in 1975 and managed as a split-split-plot arrangement of rotation (winter wheat-grain sorghum-fallow) with three tillage systems (conventional tillage (CT), reduced tillage (RT), and no-tillage (NT)), and four N application rates (0, 20, 40, and 60 lb N/a) in a randomized complete block design. Results were analyzed using analysis of variance and stability analysis. Yields of winter wheat and grain sorghum significantly decreased with decreases in both tillage intensity and N fertilizer rates. The mean yield for winter wheat was significantly correlated with total precipitation but was not correlated with precipitation during fallow periods or during the growing season. Wheat yield and total precipitation were correlated for the highest N fertilizer rates across all tillage treatments, but not for low N fertilizer rates. Grain sorghum yield was correlated with precipitation during the growing season, particularly for the highest N fertilizer rates. The stability analysis showed grain yield with each tillage practice was more stable with increasing N fertilizer rates.
Keywords: conventional tillage; reduced tillage; no tillage; N fertilizer; yield stability; precipitation correlation; dryland systems